2004
DOI: 10.1007/978-3-540-24595-7_44
|View full text |Cite
|
Sign up to set email alerts
|

Drawing Area-Proportional Venn and Euler Diagrams

Abstract: Abstract. We consider the problem of drawing Venn diagrams for which each region's area is proportional to some weight (e.g., population or percentage) assigned to that region. These area-proportional Venn diagrams have an enhanced ability over traditional Venn diagrams to visually convey information about data sets with interacting characteristics. We develop algorithms for drawing area-proportional Venn diagrams for any population distribution over two characteristics using circles and over three characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(160 citation statements)
references
References 3 publications
1
159
0
Order By: Relevance
“…An implementation of the algorithm was also provided which had a limited guarantee of being able to draw any such diagram with up to four contours in any one connected component. In [1] the relaxation of the wellformedness conditions to allow multiple points and concurrent contours was adopted, and although no conversion from theory to practise was provided, it was shown that the Euler diagram generation problem is NP-Complete in this case. Since imposing some wellformedness conditions implies that some abstract descriptions are not realisable as Euler diagrams, in [1] the notion of an Euler diagram was extended so that any abstract description with at most nine sets could be drawn: they used Euler diagrams that had holes, which are a restricted version of allowing duplicate curve labels.…”
Section: A Amentioning
confidence: 99%
See 4 more Smart Citations
“…An implementation of the algorithm was also provided which had a limited guarantee of being able to draw any such diagram with up to four contours in any one connected component. In [1] the relaxation of the wellformedness conditions to allow multiple points and concurrent contours was adopted, and although no conversion from theory to practise was provided, it was shown that the Euler diagram generation problem is NP-Complete in this case. Since imposing some wellformedness conditions implies that some abstract descriptions are not realisable as Euler diagrams, in [1] the notion of an Euler diagram was extended so that any abstract description with at most nine sets could be drawn: they used Euler diagrams that had holes, which are a restricted version of allowing duplicate curve labels.…”
Section: A Amentioning
confidence: 99%
“…To guarantee to find a wellconnected planar dual where one exists is an NPComplete problem [1]. Therefore we resort to heuristics to do as good a job as possible.…”
Section: Edge Removal To Achieve Planaritymentioning
confidence: 99%
See 3 more Smart Citations